Race relations in Ceará and the raid of black jangadeiros at the time of Lei Afonso Arinos (1951-1958) (PerCursos, 2024)
The focus of the article is racial relations in the state of Ceará in the 1950s. Its objective is to understand how the printed matter, in the 1950s, treated the racial identity of the Ceará fissherman who carried out  in to raid in their fight for labor rights at the time of creation of the Afonso Arinos Law (1951). Examinations of the printed matter will have as a limit the year 1958, the year of the article published by Ceará columnist Adísia Sá in the context of the First National Congress of Black People in Porto Alegre. Using the content analysis method proposed by Bardin (2009), journalistic articles are in the process of being analyzed. The printed photographs are also being analyzed in the light of Miriam Moreira Leite (1993). The study, based on Gilberto Freyre (1967), Parsifal Barroso (1969), Lélia Gonzalez (1984) and Roberto Damatta (2000) points to the conclusion that, by denying racism and the contribution of black people to regional identity, Through the racial identification of fissherman as “caboclos”, a “Cearense-style racism” was reproduced in Ceará.
Keywords: fissherman; black identity; “caboclo”; cearense-style racism; printed